Preparation and structural properties of multi-phases Nanocrystalline CaCu3Ti4O12 (Journal of the College of Basic Education, 2022)
Nanocrystalline multiphase CaCu3Ti4O12 (CCTO) was prepared using CaNO2.6H2O , CuNO2.2H2O , TiO 2and oxalic acide. Effect of pH has been studied from the phase formation behavior of the CCTO powder wherein the pH was varied 3, 5, 6, 7, 8, and 11. It is found that the multiphase are content a TiO2, CuO, CaTiO3 and CCTO as shown on XRD result. The crystallite size was about 60 nm according to XRD result using Scherrer,s equation. The color of prepared (CCTO) powder was light blue at room temperature, then it changes to brown and dark brown when annealing at 800oC and 900oC respectively which can attributed to demerit second phase. Carbonate groups were observed in the prepared powder calcined 900oC at pH equals to 6 and 7 that showed at FTIR spectroscopy as a vibration peaks. These groups were not showed in powder calcined 900oC at pH equals to 5. FTIR and XRD results have confirmed that the pH value for preparing multi phases CCTO is 5.